Prevalence of overweight and obesity in Portugal: results from the First Portuguese Health Examination Survey (INSEF 2015) - Gaio, Vânia (2018)
Obesity is recognised as a serious public health issue, due to its associated morbidity and mortality. This study aimed at estimating the prevalence of overweight and obesity in the Portuguese population through direct measurements obtained by the 1st National Health Examination Survey (INSEF 2015) and to identify its associated sociodemographic factors. INSEF was a nationally representative cross-sectional prevalence study conducted on 4911 Portuguese adults aged 25-74 years, in 2015. Height and weight were measured according to the European Health Examination Survey procedures. Poisson regression was used to estimate the adjusted prevalence ratios of overweight and obesity according to age, marital status, occupational activity, education, urbanization of living area and smoking status. Overall prevalences of overweight and obesity were 39.1% and 28.6%, respectively. The prevalence of overweight was higher among men (45.5% vs 33.2%) while the prevalence of obesity was higher among women (32% vs 25%). The sociodemographic factors associated with overweight and obesity were age, marital status and education. Smoking status was associated with overweight and obesity but only in women. INSEF suggests that a high prevalences of overweight and obesity are found in older individuals, married, with lower education levels and non-smoking women. Public health interventions are urgently required for obesity prevention, namely throughout health literacy strategies.